Lost in Transition: The Influence of Locus of Control on Delaying Educational Decisions - Katharina Jaik; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2016)
The transition from compulsory schooling to upper-secondary education is a crucial and frequently difficult step in the educational career of young people. In this study, we analyze the impact of one non-cognitive skill, locus of control, on the intention and the decision to delay the transition into post-compulsory education in Switzerland. We find that locus of control, measured at ages 13–14, has a significant impact on the intention to delay the transition into upper-secondary education. Furthermore, we find that the intention to delay the transition is strongly correlated with the actual delay, measured one and a half years after the intention. Finally, students with the initial intention to delay but successfully continuing into upper-secondary education show a stronger internal locus of control than comparable students who do delay their transition.
Keywords: I21; J24; 330; locus of control; school-to-school transition; school-to-work transition